Decompressive craniotomy: prognostic factors and complications in 89 patients - Faleiro,Rodrigo Moreira (2008)
Decompressive craniotomy (DC) is applied to treat post-traumatic intracranial hypertension (ICH). The purpose of this study is to identify prognostic factors and complications of unilateral DC. Eighty-nine patients submited to unilateral DC were retrospectively analyzed over a period of 30 months. Qui square independent test and Fisher test were used to identify prognostic factors. The majority of patients were male (87%). Traffic accidents had occurred in 47% of the cases. 64% of the patients had suffered severe head injury, while pupillary abnormalities were already present in 34%. Brain swelling plus acute subdural hematoma were the most common tomographic findings (64%). Complications occurred in 34.8% of the patients: subdural effusions in 10 (11.2%), hydrocephalus in 7 (7.9%) and infection in 14 (15.7%). The admittance Glasgow coma scale was a statistically significant predictor of outcome ( p=0.0309).